Vaccination coverage and associated factors among children aged 12 – 23 months in Northwest Ethiopia. Issue 10 (3rd October 2018) - Tesfaye, Tadesse Dagget; Temesgen, Worku Animaw; Kasa, Ayele Semachew
ABSTRACT: Background : Full vaccination coverage has been identified as the foundation for the prevention of morbidity and mortality from the childhood illnesses. However, a significant number of children do not get recommended vaccinations. The problem is much worse in low-income countries with varied figures and evidence gap. Therefore, this study was conducted to assess vaccination coverage and its predicting factors in one of the low-income country Ethiopia, particularly in northwest Ethiopia. Methods : A community-based cross-sectional study was conducted in Northwest Ethiopia in 2016 on 846 children aged 12 to 23 completed months. Cluster sampling method was used. Mothers or caretakers were interviewed. SPSS version 20 was used for analysis. Results : In Northwest Ethiopia, full-vaccination coverage for the children aged 12–23 months was 58.4%, while 17% and 24.6% were partially vaccinated and not vaccinated at all respectively. Child full vaccination status has a positive association with urban residence, having antenatal care visit, institutional delivery for the study child, vaccination site at health institutions, mothers who knows vaccination schedule of a catchment area, and mothers taking a child for vaccination even if the child is sick. However, mothers who ever-married and their travel time to the nearest vaccination site ≤ 30 minutes were negatively associated with child full-vaccination status. Conclusion : Vaccination coverage in Northwest Ethiopia, East Gojam, is better than the national coverage. Yet, it is far below the plan. Encouraging antenatal care utilization, delivery at health institutions, and providing adequate information on child vaccination (including when to start, return and finish) for mothers would increase full-vaccination coverage.